Program Multidisiplin Pasien Gagal Jantung Kronik untuk Menurunkan Angka Perawatan Ulang Rumah Sakit - Lusiani, Lusiani; Adnan, Nurhayati (Jurnal Penyakit Dalam Indonesia, 2024)
Heart failure is a complex disease caused by abnormalities in the structure or function of the heart resulting in decreased cardiac output. The complexity of heart failure causes an increasing burden of mortality and morbidity. This has further exacerbated the burden of treatment costs as well as the high rate of hospital readmissions. Readmission rate in patients with heart failure within 30 days post-hospitalization can reach 17.5%. In order to reduce re-hospitalization rates, multidisciplinary programs were introduced. The program involves collaboration of cardiologists, specialty nurses, pharmacists, nutritionists, and social workers using home or clinic-based models. Studies show that special management programs with a multidisciplinary approach can reduce re-hospitalization, mortality, and morbidity in heart failure patients. Multidisciplinary programs can also increase the level of medication adherence in heart failure patients. Therefore, multidisciplinary programs can be considered as one of the main lines in the management of heart failure.